2020
DOI: 10.1093/mnras/staa3906
|View full text |Cite
|
Sign up to set email alerts
|

On the flaring of thick discs of galaxies: insights from simulations

Abstract: Using simulated galaxies in their cosmological context, we analyse how the flaring of mono-age populations (MAPs) influences the flaring and the age structure of geometrically defined thick discs. We also explore under which circumstances the geometric thin and thick discs are meaningfully distinct components, or are part of a single continuous structure as in the Milky Way. We find that flat thick discs are created when MAPs barely flare or have low surface density at the radius where they start flaring. When… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 99 publications
(137 reference statements)
1
2
0
Order By: Relevance
“…Our flared vertical profiles for the thin and thick disks are in good agreement with the predection of thin+thick flaring disk model (López-Corredoira & Molgo 2014), and are consistent with the number simulations of the chemodynamical evolution in Galactic disks formed in the cosmological context (Minchev et al 2013(Minchev et al , 2014(Minchev et al , 2015(Minchev et al , 2017, as well as the cosmological zoom simulation of VINTERGATAN (Agertz et al 2020). These model simulations suggest that the vertical flaring trends are a natural consequence of inside out, up-side down growth coupled with disk flaring (see also Bird et al 2013;García de la Cruz et al 2021), which allows for the low-[α/Fe] stars to exist several kpc above the disk's midplane. As analyzed by B16, the exponential flaring profiles for the low-[α/Fe] MAPs suggests that radial migration played an important role in the formation and evolution of the thin disk.…”
Section: Stellar Populations and Disk Structuresupporting
confidence: 85%
“…Our flared vertical profiles for the thin and thick disks are in good agreement with the predection of thin+thick flaring disk model (López-Corredoira & Molgo 2014), and are consistent with the number simulations of the chemodynamical evolution in Galactic disks formed in the cosmological context (Minchev et al 2013(Minchev et al , 2014(Minchev et al , 2015(Minchev et al , 2017, as well as the cosmological zoom simulation of VINTERGATAN (Agertz et al 2020). These model simulations suggest that the vertical flaring trends are a natural consequence of inside out, up-side down growth coupled with disk flaring (see also Bird et al 2013;García de la Cruz et al 2021), which allows for the low-[α/Fe] stars to exist several kpc above the disk's midplane. As analyzed by B16, the exponential flaring profiles for the low-[α/Fe] MAPs suggests that radial migration played an important role in the formation and evolution of the thin disk.…”
Section: Stellar Populations and Disk Structuresupporting
confidence: 85%
“…López-Corredoira & Molgó (2014) showed that the Galactic disc flares substantially between Galactocentric radii 8 kpc to 25 kpc (also see Li et al 2019) with the thin-disc component having a scale-height of ∼ 300 pc in the Solar neighbourhood (e. g., see Jurić et al 2008). This flaring of galactic disc (i.e., increment of scale-height) is a generic phenomenon (e.g., see de Grijs & Peletier 1997;Narayan & Jog 2002a;Sarkar & Jog 2019;García de la Cruz et al 2021). In addition, the existence of a thick-disc component is now wellestablished observationally in both, external galaxies, as well as the Milky Way (e.g., see Tsikoudi 1979;Burstein 1979;Yoachim & Dalcanton 2006;Comerón et al 2011aComerón et al ,b, 2018.…”
Section: Introductionmentioning
confidence: 93%
“…increment of the scale height) is a generic phenomenon (e.g. see de Grijs & Peletier 1997;Narayan & Jog 2002a;Sarkar & Jog 2019; García de la Cruz et al 2021). In addition, the existence of a thick-disc component is now well established observationally in external galaxies as well as in the Milky Way (e.g.…”
Section: Introductionmentioning
confidence: 99%